ANALISIS UPAYA GURU MENGATASI KESULITAN BELAJAR PESERTA DIDIK KELAS VI SEKOLAH DASAR - Rizki Adri Yohanes; Hafsemi Rapsanjani; Fredy Fredy (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Problems experienced by students in learning will affect student learning outcomes. Each student has different learning difficulties. Therefore, the teacher should make efforts to overcome students' learning difficulties. Based on this, researchers conducted research to describe the efforts made by teachers to overcome learning difficulties experienced by students. This research is qualitative research with the type of phenomenological research. The data collected in this study came from interviews and observations. The study results show several stages the teacher carried out in overcoming learning difficulties. These stages are the identification stage, the diagnosis stage, the prognosis stage, and the stage of providing action or assistance. At the identification stage, the teacher makes direct observations to find out the problems faced by students. At the diagnosis stage, the teacher collects data to know the types of problems faced by students. The teacher's prognosis stage carries out planning to plan actions or forms of assistance that will be given to students. The stage of providing action or assistance is by carrying out the planned actions. In this study, the teacher provided assistance such as group study guidance, individual guidance, or various learning methods.